1990
DOI: 10.1152/ajpheart.1990.258.2.h610
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release from cardiac sarcoplasmic reticulum induced by photorelease of calcium or Ins(1,4,5)P3

Abstract: The ability of Ca2+ or inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] to release Ca2+ from cardiac sarcoplasmic reticulum (SR) was investigated using saponin-skinned ventricular trabeculae from rats. To overcome diffusion delays, rapid increases in the concentrations of Ca2+ and Ins(1,4,5)P3 were produced by laser photolysis of "caged Ca2+" (Nitr-5) and "caged Ins(1,4,5)P3". Photolysis of Nitr-5 to produce a small jump in [Ca2+] from pCa 6.8 to 6.4 induced a large and rapid force response (t1/2 = 0.89 s at 12 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…Inositol (1,4,5)trisphosphate is rapidly released into the cytoplasm, activates inositol(1,4,5) trisphosphate receptors in the sarcoplamic reticulum and causes Ca 2+ release from the sarcoplamic reticulum, which leads to vasoconstriction (Kleinz and Davenport, 2005). In normal cardiac cells, however, inositol(1,4,5)trisphosphate induced Ca 2+ release seems rather slow (Kentish et al, 1990). Nevertheless, it is known that Ca 2+ release from the sarcolpasmic reticulum is diminished as a result of hyperphosphorylation of the ryanodine receptors (Marks et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Inositol (1,4,5)trisphosphate is rapidly released into the cytoplasm, activates inositol(1,4,5) trisphosphate receptors in the sarcoplamic reticulum and causes Ca 2+ release from the sarcoplamic reticulum, which leads to vasoconstriction (Kleinz and Davenport, 2005). In normal cardiac cells, however, inositol(1,4,5)trisphosphate induced Ca 2+ release seems rather slow (Kentish et al, 1990). Nevertheless, it is known that Ca 2+ release from the sarcolpasmic reticulum is diminished as a result of hyperphosphorylation of the ryanodine receptors (Marks et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies on isolated animal ventricular fibers have shown that IP3 triggers calcium release from the SR (26) and potentiates the effects of caffeine-induced calcium release (27). Northern blot analyses using the cloned murine IP3R cDNA as a probe have identified the -10-kb IP3R mRNA in various mouse tissues, including the heart (7,28).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the notion that IP 3 mediates Ca 2+ release in the heart is not new, and has been established by studies spanning the last two decades. The very earliest studies on cardiac IP 3 signaling found evidence for functional IP 3 Rs capable of releasing Ca 2+ from the SR [47][48][49][50][51]. However, compared with Ca 2+ -induced Ca 2+ release through RyRs, though, the IP 3 -induced Ca 2+ release was slow and small.…”
Section: The Dilemma Of Cardiac Ip 3 Receptors: Lost In An Ocean Of Rmentioning
confidence: 99%